Circularly Polarized Microstrip Array Antenna for Ground Segment in Quasi-Zenith Satellite System - Zulkifli, Fitri Yuli; Rahardjo, Eko Tjipto (UI Scholars Hub, 2012)
In satellite communication system, antenna plays an important role. Therefore, the antenna must meet some requirements, such as high gain, circular polarization, and good directivity. In this paper, a four element linear array triangular patch microstrip antenna with cross slot is designed to be used for Quasi-Zenith satellite system. A simulation study as well as experimental study was carried out. The simulation showed that the 3 dB axial ratio bandwidth of 87 MHz (2.569-2.656 GHz) is achieved while the measured results showed 96 MHz (2.556-2.652 GHz). The linear array of 4 element antenna has a gain of 13.73 dB and maximum radiation pattern at 40° and -40°. Simulation and experiment results show that this antenna has met the characteristic requirements of Quasi-Zenith satellite.